The Realm of Fiqh and Quiddity of Permissibility; A Review of the Principle “عدم خلوّ الواقعة عن الحکم There is no Event without Legal Ruling” - Mohsen Jahangiri; Muhammad Ali Bannaei Kheyrabadi (آموزه‌‌های فقه مدني, 2022)
The problem of the realm of fiqh relates with an extensive network of subjects which each has been propounded in its specific area. One of the effective subjects to solve this problem is to extract the quiddity of legal rules to get its range. Explaining the quiddity of permissibility (Arabic: اباحه ibahah) and mentioning the permissibility is the absence of legal ruling or the ruling of permissibility has a vital role in the problem of the fiqh realm. Especially, when the relationship between permissibility (Arabic: اباحه ibahah) with the principle “عدم خلوّ” is described well; a continual principle -according to claim a consensus on it- in Shia fiqh and the principles of fiqh which its contents are: no events are without legal ruling “عدم خلوّ الواقعة عن الحکم”. Besides the naqlior revealed arguments “everything -halal or haram or what people need- but it is in the holy Quran or Islamic tradition” martyr Sadr for proving this has utilized the reasoning argument i.e. God’s grace. Although the principle of grace (lutf) is considered valid and has a great effect in the problems such as the comprehensiveness of sharia, the relationship between fiqh and law but it has not appropriately clarified as the position of the jurist such as Imam Khomeini with adducing to some of his sayings in the absence of his important analysis of permissibility and the absence of ruling has been gathered. The present note with referring to the authentic Shia usul and fiqh texts and with jurisprudential method the opponents’ opinions of this principle such as Muhaqiq Naraqi, the late grand Ayatollah Khoei and Imam Khomeini have been surveyed and at the end with close attention to the space of issuance of narrations and debate on reasoning argument of God’s grace it has valued (believed) the authenticity of some opponents’ reasons.